In Vitro Fermentation Characteristics of Pelagic Sargassum for Inclusion in Integral Diets for Ruminants - Luis Alberto Canul-Ku; Fernando Casanova-Lugo; Edgar Aguilar-Urquizo; Ingrid Valdivieso-Pérez; Darwin Arcos-Álvarez; Jorge Canul-Solís; Luis Castillo-Sánchez; Alfonso Chay-Canul; Benito Dzib-Castillo; Angel Piñeiro-Vázquez (Fermentation)
Pelagic sargassum arriving in the Mexican Caribbean is a mixture of brown macroalgae containing polysaccharides, minerals, and secondary metabolites with potential in ruminant diets. The objective of the present study was to evaluate the effect of the inclusion of sargassum in integral diets (ID) on in vitro fermentation characteristics. A completely randomized design was used. The treatments were different levels of sargassum (ICD: 0%, ID10: 10%, ID20: 20% and ID30: 30%) added to a basal substrate (a mixture of Pennisetum purpureum Vc. CT-115 hay, corn, soybean, and molasses). Rumen fluid was obtained from five male lambs with a body weight of 40 ± 3 kg. In vitro gas production (IVGP) as well as dry matter degradability (DMD) and organic matter degradability (DOM) increased linearly (p < 0.0001) as the proportion of sargassum increased at 24, 48, and 72 h. Rumen fluid pH decreased (p < 0.05) with 30% inclusion at 48 h, while protozoan concentration was similar (p > 0.05) in all treatments with respect to the control at all evaluation times. These results indicate that the inclusion of pelagic sargassum in integral concentrated diets improves fermentative parameters, and its inclusion in diets for ruminants is feasible. This opens up a window of opportunity for its study as a novel additive or unconventional supplement. However, in vivo studies are necessary to rule out harmful effects on animal health and performance.